CONSTRUCTING CHINA'S IMAGE IN WESTERN AND UKRAINIAN MEDIA: A LINGUISTIC ANALYSIS OF METAPHORICAL EXPRESSIONS - Qin, Song (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The formation of China’s national identity in the global context is a crucial aspect of modern media discourse, significantly influencing the country’s perception on the international stage. The critical analysis of linguistic manipulations and discursive strategies used in the media is particularly relevant because, in the era of globalization, media has become a powerful tool in shaping public opinion. Therefore, it is important to investigate how linguistic manipulations affect China’s image, especially in the context of intercultural communication.The study employs methods of cognitive linguistics and discourse analysis, which involve both quantitative and qualitative analysis of media texts. The quantitative analysis reveals the frequency of specific lexical units and rhetorical figures that impact the construction of China’s image, while the qualitative analysis provides deeper insight into the conceptual metaphors and communicative strategies used to create narratives that reflect social and cultural contexts.It was found that linguistic manipulations in the media significantly influence the perception of China as a country on the international stage, shaping both positive and negative narratives. Specific rhetorical techniques employed in the media can either emphasize or diminish the country’s image. The quantitative analysis demonstrated the presence of manipulative aspects in media discourse, while the qualitative analysis revealed the intentionality of communicative strategies that shape the audience’s perception of China.The findings confirm that a critical analysis of media content, with a focus on linguistic and discursive strategies, is essential for understanding contemporary sociocultural processes and international relations. Linguistic manipulations in the media are a significant aspect that requires further study within the context of globalization. The research on China’s image in the media not only uncovers the mechanisms of national identity construction but also highlights the importance of considering cultural and social contexts that affect the perception of the country.____________References:• Bondarenko, Y. O. (2019). Conceptual metaphors as a manifestation of cognitive activity of a linguistic personality in modern English and Ukrainian journalistic discourse. http://rep.knlu.edu.ua/xmlui/ bitstream/handle/787878787/1328/Nvkyu_2019_38_4.pdf?sequence=1&isAllowed=y• Lavrukhin, V. L. (2021). Cognitive metaphor as a discursive means of representing authorial intentions. http://zfs–journal.uzhnu.uz.ua/ archive/26/part_1/34.pdf• Striuk, T. (2020). The potential of cognitive metaphor in the political television interview of Petro Poroshenko. https://molodyivchenyi.ua/ index.php/journal/article/view/3042• Lakoff,, & Johnson, M. (1980). Metaphors we live by. University of Chicago Press.• Wodak, (2015). Critical Discourse Analysis: History, Agenda, Theory, and Methodology. In C. Rentoumi & E. Z. Kossyva (Eds.), Critical Discourse Analysis: A Primer (pp. 78-104). Cambridge: Cambridge University Press.• Hromadske Radio. (2023, October 20). Interv’yu z Pavlom Klimkinym. Davshy Ukrayini ATACMS, SSHA pidnyaly stavky [Interview with Pavlo Klimkin. By giving Ukraine ATACMS, the USA raised the stakes]. https://hromadske.radio/podcasts/tsey-tyzhden/davshy-ukraini-atacms-ssha-pidnialy-stavky-pavlo-klimkin• Ekonomichna Pravda. (2019, June 8). Posol Italiyi: Ukrayina - tse nastupne ekonomichne dyvo, malenʹkyy Kytay [Ambassador of Italy: Ukraine is the next economic miracle, a small China]. https://epravda.com.ua/news/2019/06/8/648580/• Ekonomichna Pravda. (2023, August 21). WSJ zayavyla pro "zanepad" 40-richnoho ekonomichnoho bumu v Kytayi, Liya Ilʹchenko [WSJ reported on the "decline" of the 40-year economic boom in China, Liya Ilchenko]. https://epravda.com.ua/news/2023/08/21/703420/• Radio Svoboda. (2021, October 1). Kytaysʹki investytsiyi v Ukrayini: vikno mozhlyvostey chy ryzyk? Solonyna Yevhen [Chinese investments in Ukraine: a window of opportunities or a risk? Yevhen Solonyna]. https://www.radiosvoboda.org/a/kytai-ukrayina-investytsiyi-kredyty-knr-kpk/31487078.html• Radio Svoboda. (2024, March 23). De «liniya Zelensʹkoho»? Khto mav pobuduvaty fortyfikatsiyi i shcho z nymy teper, Katsan Olʹha [Where is the "Zelensky line"? Who was supposed to build the fortifications and what happened to them now? Olga Katsan]. https://www.radiosvoboda.org/a/shcho-vidbuvayet%CA%B9sya-z-fortyfikatsiyamy/32873058.html• Slovo i Dilo. (2023, March 2). Kytay yak torhovelʹnyy partner Ukrayiny: yak zminyuvalysya obsya hy eksportu ta importu [China as a trade partner of Ukraine: how export and import volumes have changed]. https://www.slovoidilo.ua/2023/03/02/infografika/ekonomika/kytaj-yak-torhovelnyj-partner-ukrayiny-yak-zminyuvalysya-obsyahy-eksportu-ta-importu• Ukrinform. (2024, July 17). Kytay mozhe zihraty produktyvnu rolʹ u prypynenni viyny v Ukrayini – Derzhdep [China can play a productive role in ending the war in Ukraine – U.S. State Department]. https://www.ukrinform.ua/rubric-world/3886032-kitaj-moze-zigrati-produktivnu-rol-u-pripinenni-vijni-v-ukraini-derzdep.html• EconomistUA. (2023, November 3). Filosofiya, biznes ta yednistʹ u rozvytku: Yak kontseptsiya konfutsiantsva zminyla suchasnyy Kytay [Philosophy, business, and unity in development: How Confucianism's concept changed modern China]. https://economistua.com/filosofiya-biznes-ta-yednist-u-rozvytku-yak-kontseptsiya-konfutsianstva-zminyla-suchasnyj-kytaj/• Facebook. (2024). Komentar Olena: "Chy varto nam spivpratsyuvaty z krayinoyu, de nemaye svobody slova?" [Comment by Olena: "Should we cooperate with a country where there is no freedom of speech?"]. https://facebook.com• (2024). Komentar @GlobalInsight: “Kytaj stav ekonomichnym dyvom, yake varto vyvchaty”. [Comment by @GlobalInsight: “China became an economic miracle worth studying”]. https://twitter.com• ВВС. (2024, April 16). China economy grows faster than expected in first quarter, Mariko Oi. https://www.bbc.com/news/business-68823396• Blog by William A. (2019, February 14). China’s Great Wall reminds us that walls are not good or evil. What’s important is who controls who flows through them. https://www.google.com/search?q=China%E2%80%99s+Great+Wall%3A+A+Symbol+of+Isolation%3F&oq=China%E2%80%99s+Great+Wall%3A+A+Symbol+of+Isolation%3F&gs_lcrp=EgZjaHJvbWUyBggAEEUYOdIBCTIwMDJqMGoxNagCCLACAQ&sourceid=chrome&ie=UTF-8• (2024, September 16). China's access to Western markets is reshaping globalization, Djoomart Otorbaev. https://news.cgtn.com/news/2024-09-16/China-s-access-to-Western-markets-is-reshaping-globalization-1wWdC7e8T6M/p.html• Global Times. (2024). China as a key global growth driver. https://www.globaltimes.cn/page/202403/1309390.shtml• (2024). https://www.instagram.com/vunderkind_z_pelushok/p/китай-це-древня-країна-з-тисячолітньою-історією-і-культурою-приказки-та-прислівя/• Published online by Cambridge University Press. (2022, June 6). Questions for Hierarchical Confucianism. Ziliotti Elena. https://www.cambridge.org/core/journals/review-of-politics/article/questions-for-hierarchical-confucianism/475508468FB332C9825395B6F2D5C0BF?utm_source=chatgpt.com• The Economist. (2024, June 15). China has become a scientific superpower. https://www.economist.com/science-and-technology/2024/06/12/china-has-become-a-scientific-superpower• The Guardian. (2024, May 1). China erases memory of ‘white paper’ protests in further threat to journalism. https://www.theguardian.com/global-development/2024/may/01/chinas-authorities-erase-memory-white-paper-protests-in-tightening-of-censorship-press-freedom• The New York Times. (2022, November 28). Chinese Unrest Over Lockdown Upends Global Economic Outlook, Patricia Cohen. https://www.nytimes.com/2022/11/28/business/economy /china-unrest-global-economy.html• The World Economic Forum. (2024, June 27). Where is China’s economy headed? https://www.weforum.org/stories/2024/06/china-economic-outlook-growth-trade/• (2024). https://www.tiktok.com• United World International. (2024, June 13). The “Chinese dragon” is awakening, and the “American Empire” is tottering in the sands of the Middle East. https://unitedworldint.com/35024-the-chinese-dragon-is-awakening-and-the-american-empire-is-tottering-in-the-sands-of-the-middle-east/• (2024, April 18). Chine: Un Géant Économique à l’Avenir Incertain. https://www.veracash.com/fr/blog/chine-un-geant-economique-a-lavenir-incertain#:~:text=Le%20PIB%20chinois%2C%20qui%20%C3%A9tait,25%20000%20milliards%20de%20dollars%20.
Keywords: linguistic manipulation, national identity, media discourse, Chinese image, cognitive linguistics, discourse analysis, intercultural communication